Bibliometric Analysis of Research Trends on Utilisation of Low-Cost Sensor (LCS) and Internet of Things (IoT) for PM2.5 Air Pollution Monitoring - Santoso, M.Sc, Dian Hudawan; Santosa, Sri Juari; Sekaranom, Andung Bayu (Universitas Pembangunan Nasional (UPN), 2024)
This investigation elucidates the inadequacies inherent in conventional air pollution monitoring methodologies, advocating for the implementation of Low-Cost Sensors (LCS) and the Internet of Things (IoT) as pioneering alternatives, specifically for the surveillance of Particulate Matter 2.5 (PM2.5). Through the execution of a bibliometric analysis, this research endeavors to assess the evolution of academic literature from 2014 to 2023, discerning principal trends, notable authors, leading nations, and prospective avenues for research. The originality of this study is manifested in its recognition of a marked escalation in this domain, particularly since 2019, alongside the burgeoning significance of LCS and IoT as economically feasible solutions for air quality governance. Scholars from emerging nations, such as Indonesia, are underscored as possessing distinctive prospects to engage in this proliferating field of inquiry, particularly in the realm of environmental management. Metadata was systematically amassed via Scopus utilizing pertinent keywords and subjected to analysis employing Biblioshiny and Vosviewer software, uncovering a pronounced increase in publications, notably in 2022. Distinguished authors include Alam F, Ali S, and Potgieter J. The results suggest that forthcoming research and practical implementations of LCS and IoT for PM2.5 monitoring possess substantial promise, presenting a fruitful pathway for tackling air quality issues on a global scale.